2015
DOI: 10.1007/s00247-015-3350-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ultrasound elastography in detecting active myositis in children: can it replace MRI?

Abstract: Compression-strain US elastography does not accurately detect active myositis in children with juvenile idiopathic inflammatory myopathy and cannot replace MRI as the imaging standard for detecting myositis in these children. The association between abnormal US elastography and increased muscle echogenicity suggests that elastography is capable of detecting muscle derangement in patients with myositis; however further studies are required to determine the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
(38 reference statements)
0
20
1
Order By: Relevance
“…Potential underlying mechanisms include increased intra- and extra-cellular water content in the case of oedema and loss of myofibre contractile properties in atrophy. However, this association is in contrast to the findings of Song et al [ 16 ] and Berko et al [ 17 ], who reported no statistically significant correlation using strain elastography. The technical and mechanical factors of strain elastography may have limited its capability to detect the myositis-induced elasticity changes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Potential underlying mechanisms include increased intra- and extra-cellular water content in the case of oedema and loss of myofibre contractile properties in atrophy. However, this association is in contrast to the findings of Song et al [ 16 ] and Berko et al [ 17 ], who reported no statistically significant correlation using strain elastography. The technical and mechanical factors of strain elastography may have limited its capability to detect the myositis-induced elasticity changes.…”
Section: Discussioncontrasting
confidence: 99%
“…The failure of muscle elastography to correlate with IIM disease activity was reported by Song et al [ 16 ] and Berko et al [ 17 ]. The latter, however, used the physician’s grading of disease activity as the measure instead of CK.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This information was then used to guide botulinum toxin injections [6]. Elastography has also been applied in the evaluation of inflammatory myopathies [35,36]. Botar‐Jid et al evaluated patients with inflammatory muscle diseases including dermatomyositis and polymyositis and found concordance between the elastography colorgram and serum creatine kinase and lactic dehydrogenase markers [36].…”
Section: Sonoelastographymentioning
confidence: 99%
“…Botar-Jid et al evaluated patients with inflammatory muscle diseases including dermatomyositis and polymyositis and found concordance between the elastography colorgram and serum creatine kinase and lactic dehydrogenase markers [36]. However, other studies have suggested that sonoelastography does not accurately detect active myositis in children with juvenile idiopathic inflammatory myopathy as compared to the gold standard of MRI [35]. Sonoelastography has more established literature supporting its use in the evaluation of tendon disorders; further studies are needed to define its role in the evaluation of muscle disorders.…”
Section: Sonoelastographymentioning
confidence: 99%